2021
DOI: 10.1177/10298649211015278
|View full text |Cite
|
Sign up to set email alerts
|

Perception and learning of relative pitch by musicians using the vibrotactile mode

Abstract: This study investigated the perception and learning of relative pitch using vibrotactile stimuli by musicians with and without a hearing impairment. Notes from C3 to B4 were presented to the fingertip and forefoot. Pre- and post-training tests in which 420 pairs of notes were presented randomly were carried out without any feedback to participants. After the pre-training test, 16 short training sessions were carried out over six weeks with 72 pairs of notes per session and participants told whether their answe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…CI users often have considerable difficulties when singing, particularly in producing the correct pitch (Xu et al, 2009;Mao et al, 2013). There have been some promising results when providing pitch information to hearing-impaired listeners through haptic stimulation to improve singing (Sakajiri et al, 2010(Sakajiri et al, , 2013Shin et al, 2020;Hopkins et al, 2021). Future work should establish the effectiveness of the alternative pitch-based haptic stimulation approach suggested by Fletcher et al (2020c), which was shown to provide high-resolution pitch information.…”
Section: Discussionmentioning
confidence: 99%
“…CI users often have considerable difficulties when singing, particularly in producing the correct pitch (Xu et al, 2009;Mao et al, 2013). There have been some promising results when providing pitch information to hearing-impaired listeners through haptic stimulation to improve singing (Sakajiri et al, 2010(Sakajiri et al, , 2013Shin et al, 2020;Hopkins et al, 2021). Future work should establish the effectiveness of the alternative pitch-based haptic stimulation approach suggested by Fletcher et al (2020c), which was shown to provide high-resolution pitch information.…”
Section: Discussionmentioning
confidence: 99%
“…Son particularmente interesantes los estudios de Carl Hopkins et al (2016) sobre la discriminación de los tonos de la escala musical occidental aplicando vibraciones táctiles con la frecuencia pura de cada tono en la yema de los dedos y en la planta del pie de los sujetos. Los resultados de sus investigaciones muestran que el rango de notas musicales que pueden considerarse para la presentación vibro-táctil de la música comprende desde la nota C1 (es decir el Do de la octava más baja del piano 32,70 Hz) hasta la nota G5 (la nota Sol de la quinta octava del piano 783,99 Hz), aunque este umbral se puede ampliarse aumentando la amplitud de la estimulación táctil por encima del umbral medio y con entrenamiento (Hopkins et al, 2023). A la hora de generar el estímulo táctil hay que tener especial cuidado con la amplitud ya que el rango de discriminación tonal puede verse afectado por los niveles de amplitud con los que se genera el estímulo (Brewster y Brown, 2004).…”
Section: Percepción Vibrotáctil De Parámetros Musicalesunclassified
“…Archetype of a vibrotactile augmentation system. (Hopkins et al, 2021). The last musical dimension that researchers focus on in terms of its vibrotactile properties is the timbre-the tempo-spectral characteristics of the stimulation that translates into the perceived quality of the sound, anecdotally refereed to as the color of sound or tone color.…”
Section: Figurementioning
confidence: 99%